Analysis Of Determinants Of The Influence Of The Use Of The HiDOK Application As An Online Registration In Moderating The Effect Of Service Quality, Trust, And Hospital Image On Patient Satisfaction At Kasih Ibu Tabanan Hospital - Ni Gusti Ayu Made Sri Pujarini; Gede Sri Darma (Green Publisher Indonesia, 2024)
In the era of technological advancement, providing excellent service has become a crucial element for business sustainability, especially in the healthcare sector. Kasih Ibu Tabanan Hospital, as a provider of comprehensive healthcare services, continues to strive to improve the quality of its services through the implementation of the HiDok application for online registration. This research aims to examine the influence of service quality, trust, and hospital image on patient satisfaction, as well as to evaluate the moderating role of the HiDok application in these relationships. Using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach, data were collected from 175 patients of Kasih Ibu Tabanan Hospital in December 2023. The results of the study are expected to contribute to the development of marketing science in the healthcare field and provide practical guidance for hospital management in enhancing patient satisfaction through online registration technology.